The factors influencing online fruit purchasing in Thailand by using consumer to community to business model and grey relational analysis - Tzong-Ru Lee; Nawapan Kaewsainun; Yaseen Murtuza Delvi; Yong-Shun Lin (LP3M Universitas Putra Bangsa, 2026)
E-commerce is a growing industry where product or service marketing is often supported by the power of influencers: individuals who affect consumers’ purchasing behaviour. In this study, a newly developed E-commerce model was employed to investigate the impacts of various individuals on consumers’ surrounding environment and media on consumers’ online purchasing intentions on general fruit products, including fresh fruits, frozen fruits, and processed fruits. Our study extends the present research regarding the reference effect on online purchasing intention. We identify the key successful factors regarding influencer marketing. Our results indicated that family members, friends, colleagues, and celebrities were the key factors in terms of influence for fresh fruits, frozen fruits, and processed fruits. Trustworthiness, product or industry expertise, credibility, and knowledge characteristics of influencers were identified as the successful factors for influencing consumers. Facebook and websites are identified as important channels of interaction between consumers and influencers for all three types of fruits.